2021
DOI: 10.3389/fnint.2021.754613
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Psychiatric Comorbidities and Psychotherapeutic Assessment in Inpatient Epilepsy Care: Preliminary Results of an Implementation Study

Abstract: Background: Anxiety and depression remain underdiagnosed in routine clinical practice in up to two thirds of epilepsy patients despite significant impact on medical and psychosocial outcome. Barriers to adequate mental health care for epilepsy and/or psychogenic non-epileptic seizures (PNES) include a lack of integrated mental health specialists and standardized procedures. This naturalistic study outlines the procedures and outcome of a recently established psychotherapeutic service.Methods: Routine screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Nearly 30% of people with convulsive epilepsy suffer from comorbid neuropsychiatric disorders, with the predominance of anxiety and depression ( Mula et al, 2021 ). The presence of psychiatric comorbidities is a negative prognostic marker that is associated with a worse response to treatment, increased morbidity, mortality, and adverse clinical outcome ( Michaelis et al, 2021 ). The burden of the commodities is even higher in people with non-convulsive epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 30% of people with convulsive epilepsy suffer from comorbid neuropsychiatric disorders, with the predominance of anxiety and depression ( Mula et al, 2021 ). The presence of psychiatric comorbidities is a negative prognostic marker that is associated with a worse response to treatment, increased morbidity, mortality, and adverse clinical outcome ( Michaelis et al, 2021 ). The burden of the commodities is even higher in people with non-convulsive epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…In this service, all seizure inpatients are given measures for depression and anxiety (Table S1). Those scoring above clinical cutoffs, and all FDS patients regardless of scores, are allocated to members of the psychotherapy team to arrange further assessment 45 …”
Section: Resultsmentioning
confidence: 99%
“…Across several publications, the RHH/EN has demonstrated that patients attending the service experience significant improvements in their mental health symptoms (e.g., trauma, depression) that remain at follow‐up 32,40,41 . The UKB/DE recently published data demonstrating that >95% of consenting participants adhered to mental health treatment plan recommendations 1 month after discharge 45 . The UKB/DE is actively collecting follow‐up data on depressive and anxiety symptoms, as well as QOL, which is currently unpublished.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations